Influence of Leadership Style, Competence, and Work Discipline on Employee Performance in Pt. Sumo Internusa Indonesia - Cut Fitri Rostina; Annisa Ramandha Putri Siahaan; Fahtin Fahtin; Talinaizisokhi Harefa; Titi Murni Gea (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to evaluate and examine the influence of leadership style, competence and work discipline on employee clinic at PT. Sumo Internusa Indonesia. The decline in the quality of employee performance is caused by the leadership style that is still lacking to control employees, competence is not in accordance with placement, and employee discipline is still minimal. The population in this study all employees who worked at PT. Sumo Internusa Indonesia. The sampling technique using saturated sampling method. The sample in this study were employees at PT. Sumo Internusa Indonesia, amounting to 79 employees. The calculation results of partial hypothesis testing in leadership style research results obtained tcount 2.501> 1.992 and a significant value of 0.015 <0.05. The competency of the research results obtained by t -0,195 <-1,992 and a significant value of 0.846> 0.05. The work discipline results of the study obtained tcount 5.485> 1.992 and a significant value of 0.000 <0.05. Fcount value obtained Fcount value of 25.085 and Ftable value of 2.72 which means Fcount> Ftable and a significant value of 0.000 <0.05. The coefficient of determination test results obtained Adjusted R Square value is 0.481, which means 48.1% in which employee performance variables can be explained by the three variables of 48.1%. While the rest (100% - 48.1% = 51.9%) is explained by other variables not examined, such as the work environment, communication, motivation and so on. The conclusions in this study indicate that partially the leadership style and work discipline have a positive effect and significant to the performance of employees at PT. Sumo Internusa Indonesia. While Competence has a negative and not significant effect on Employee Performance at PT. Sumo Internusa Indonesia. Simultaneously leadership style, competency, and work discipline together have positive and significant effect on employee performance at PT. Sumo Internusa Indonesia.